Screening of Coconut Genotypes Against Coconut Eriophyid Mite (Aceria guerreronis Keifer.) - Bagde, A. S.; Patil, P. D.; Pashte, V. V. (International Journal of Bio-resource and Stress Management, 2023)
The coconut genotypes were screened for their level of susceptibility to coconut eriophyid mite. Based on the mean damage Grade Index score none of the coconut genotypes were found to be resistant to eriophyid mite. However the genotypes, Jamica (1.37), BSI (1.51), Lono (1.65), Ganga Bondem (1.67), Banawali yellow long (1.70), Orangedwarf (1.77), Kalpwangi (1.80), F.M.S. (1.88), Guwam (1.93), West coast tall (1.82) CochinNikobar (2.01), Fiji (2.30) and Cochin China (2.35) were found to be moderately resistant to the infestation of eriophyid mite. The genotypes Seychelles (2.88), Phillipines (2.93), T×D (3.03), and Andaman Bhadi (3.09) were found to be susceptible to the eriophyid mite infestation. On the other hand the coconut genotypes SanRayman (3.35), Pratap (3.60), Banawali green long (3.60), Sheli gol (3.69), Borino (3.77), Lakshadweep (3.81), Kenya (4.22), Gawati (4.28), were found to be highly susceptible. Among the 26 coconut genotypes screened for their reaction to the coconut eriophyid mite, minimum infestation was observed in the genotypes Jamica, BSI, Lono, Guwam and Orange dwarf which are useful for the coconut growers in minimizing loss caused by eriophyid mite. Thus the impact of coconut eriophyid miteon yield parameters studied under Konkan conditions indicated that as the severity of eriophyid mite infestation increases the total weight, dehusked nut weight, husk weight, kernel weight, shell weight, length, circumference, water content loss of coconut also increase as the different damage grades increase from Grade II to Grade V.